The Effect of School Principals Integrity, Communication Atmosphere, Discipline and Achievement Motivation on Teachers’ Work Productivity at Public Vocational High School (SMK) in Padang - Ariswan Ariswan; Rusdinal Rusdinal; Muri Yusuf; Gusril Gusril (Fakultas Ilmu Pendidikan UNP)
The phenomenon in the field illustrates the low productivity of teachers in assigning tasks. This research aims to reveal the influence of: (1) Integrity of principal and work discipline to motivation of teacher achievement in SMK, (2) Integrity of principal to teacher work discipline in SMK Negeri Kota Padang, (3) Integrity of principal, work discipline and motivation achievement on teacher work productivity in SMK Negeri Kota Padang. The sample of the study amounted to 266 people. The research data was collected by Likert scale model questionnaire. Data were analyzed by moderation variable path analysis technique. The result of the research shows that: (1) There is direct and indirect influence significantly Integrity of school principal and work discipline of teacher toward achievement motivation, (2) There is direct and indirect influence significantly Integrity of principal to work discipline (3) There is direct influence and not significantly the integrity of the principal, work discipline and achievement motivation affect the productivity of teachers work.